Legal Aspects in Handling Criminal Acts in the 2019 Election - Muhammad Subhan Nurul Umam; Muhammad Pajar Sidik (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This research meticulously examines the legal framework and the procedures involved in addressing election crimes in Indonesia, as outlined in Law No. 7 of 2017, and evaluates the effectiveness of Sentra Gakkumdu, a pivotal coordination forum in the electoral crime enforcement process. The primary objective is to dissect and analyze the legal intricacies and practical challenges in enforcing laws against election crimes, with a spotlight on the ambiguities and potential conflicts within the current system. Through normative legal research methodology, the study delves into the statutory regulations and engages with various primary, secondary, and tertiary legal materials to construct a comprehensive understanding of the election crime handling procedures. It highlights the absence of clear election crime definitions, identifies several weaknesses in Law No. 7 of 2017, and critiques the ambiguous role and limited effectiveness of Sentra Gakkumdu. The paper concludes by calling for significant improvements and clarifications in the existing legal frameworks to ensure fair, efficient, and effective handling of election crimes, thereby bolstering public confidence in the electoral process and upholding the principles of legal certainty and justice in the realm of Indonesian elections.